Investigation of delay in utilization of government dental services in Malaysia - Jaafar, N.; Jalalluddin, R.L.; Razak, I.A.; Esa, R. (1992)
Although delays in seeking dental care among patients are frequently observed in daily practice, this problem has never been investigated in other utilization studies. This study attempts to establish the magnitude and severity of the problem of delay in a delivery system where cost is not a major barrier to utilization. 555 users of Government dental services were interviewed. Only 37 of them came promptly within 6 days of perceiving a dental need. The majority (63) had delayed their dental visit for more than 1 week. In fact, the highest frequency of delay was for more than 1 month. Prompt attendance was found to be associated with people who regularly came for asymptomatic check-ups. In contrast. more than 50 of those who thought they needed fillings and extractions had delayed their visit for more than a month. The main causes of delays were attributed to work commitments and the lack of perceived need for urgent care. Barriers related to transport or financial problems were ranked verv low. The implications of these findings are discussed.